Temperatures and gradients in concrete Bridges: Experimental, finite element analysis and design. (March 2022) - Abid, Sallal R.; Xue, Junqing; Liu, Jiang; Tayşi, Nildem; Liu, Yongjian; Özakça, Mustafa; Briseghella, Bruno
Abstract: Aiming to introduce a simplified flexible design model for thermal actions in concrete bridge superstructures, experimental and finite element works were carried out in this study. From an experimental concrete box-girder segment, concrete temperature, solar radiation, air temperature and wind speed records for a complete one-year cycle were recorded and utilized. In addition, a thermal finite element model was conducted and verified, which was then used to conduct required parametric studies. Finally, the verified finite element model was used together with long-term climate history (from 1960 to 2013) of 10 cities in Turkey to propose the thermal actions' design models and procedure. Both positive and negative vertical temperature gradient models were introduced in terms of the top surface maximum temperature gradient, which is related to the solar radiation history of the region. In addition, simplified correlations and design procedure were suggested to evaluate the maximum and minimum mean temperatures of concrete bridges using the long-term maximum and minimum air temperatures.